Respuesta :
Answer:
D. StartFraction negative 1 + StartRoot 3 EndRoot Over 2 EndFraction
Step-by-step explanation:
Multiply numerator and denominator by the conjugate of the denominator. Then the denominator is the difference of squares, which will be rational. This simplification is called "rationalizing the denominator."
[tex]\dfrac{1}{1+\sqrt{3}}=\dfrac{1}{1+\sqrt{3}}\cdot\dfrac{1-\sqrt{3}}{1-\sqrt{3}}=\dfrac{1-\sqrt{3}}{1^2-(\sqrt{3})^2}\\\\=\dfrac{1-\sqrt{3}}{-2}=\boxed{\dfrac{-1+\sqrt{3}}{2}}[/tex]